Do subscapularis tears really result in superior humeral migration? - Mehmet Cetinkaya; Muhammet Baybars Ataoglu; Mustafa Ozer; Tacettin Ayanoglu; Ali Yusuf Oner; Ulunay Kanatli (Acta Orthopaedica et Traumatologica Turcica, 2018)
Objectives: The aim of this study was to analyse the effect of subscapularis tear on superior humeral excursion (SHE) and acromiohumeral distance (AHD). The hypothesis was that subscapularis tears do not result in superior humeral excursion. Methods: Patients who underwent shoulder arthroscopy between August of 2011 and 2015 were reevaluated. Those with isolated Bankart lesion were used as control group and included in the Group 1, isolated full-thickness supraspinatus tear in the Group 2, isolated subscapularis tear in the Group 3, and combined subscapularis and supraspinatus tear in the Group 4. The mean SHE and AHD measurements on magnetic resonance imaging of these groups were compared to reveal any difference in superior humeral migration (SHM). Results: There were 30 patients in each group. The mean age of Group 1 (26.44 ± 8.34) was younger than the other 3 groups. The mean AHD and SHE were higher in Group 1 and 3 (Mean AHD: 12.89 ± 2.24 and 12.28 ± 1.9, respectively. Mean SHE: −3.2 ± 0.99 and −2.78 ± 0.64, respectively) than Group 2 and 4 (Mean AHD: 6.2 ± 1.78 and 6.16 ± 1.52, respectively. Mean SHE: 0.72 ± 0.65 and 1.24 ± 0.63, respectively). The AHD and SHE were strongly correlated with each other (Pearson correlation coefficient = 0.184). The inter-observer and intra-observer correlation of the measurements of SHE on MRI were excellent with intraclass correlation coefficient of 0.95 and 0.94, respectively. Conclusion: Subscapularis tears do not lead to SHM and subacromial impingement. However, superior rotator cuff tears can still lead to SHM and subacromial impingement even when subscapularis tendon is intact. Level of evidence: Level III, diagnostic study. Keywords: Arthroscopy, Shoulder, Subscapularis, Supraspinatus, Humeral migration, Humeral excursion